2010
DOI: 10.1088/1674-4926/31/6/065012
|View full text |Cite
|
Sign up to set email alerts
|

A low-power CMOS frequency synthesizer for GPS receivers

Abstract: A low-power frequency synthesizer for GPS/Galileo L1/E1 band receivers implemented in a 0.18 m CMOS process is introduced. By adding clock-controlled transistors at latch outputs to reduce the time constant at sensing time, the working frequency of the high-speed source-coupled logic prescaler supplying quadrature local oscillator signals has been increased, compared with traditional prescalers. Measurement results show that this synthesizer achieves an in-band phase noise of -87 dBc/Hz at 15 kHz offset, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Zhao Li et al [7] found that the optimal noise model for IGS reference station coordinate time series in China is not a single model, but has diversity. Yunfeng Tian et al [8] analyzed the characteristics of the correlated noise in the position time series of the GPS reference stations of the China Crustal Movement Observation Network, and found that in addition to the Flicker Noise, the correlated noise in the east component of about 50% stations can be described by FOGMRW model.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao Li et al [7] found that the optimal noise model for IGS reference station coordinate time series in China is not a single model, but has diversity. Yunfeng Tian et al [8] analyzed the characteristics of the correlated noise in the position time series of the GPS reference stations of the China Crustal Movement Observation Network, and found that in addition to the Flicker Noise, the correlated noise in the east component of about 50% stations can be described by FOGMRW model.…”
Section: Introductionmentioning
confidence: 99%